Q-enhanced tunable filter design with applications in receiver architectures - Kovala, Chelsi (Kansas State University, 2012)
Q-enhanced Filters have been researched extensively, but have not been often implemented into receiver architectures due to inherent challenges in the design and stability of these filters. However, recent works have successfully addressed Q-enhanced filter designs which are viable for receiver implementation with tuning algorithms to achieve temperature stability. This work continues these efforts with the redesign of a Two-Pole Q-Enhanced Band-Pass filter tested at narrower fractional bandwidths than previous work of less than one percent and considers potential significant improvements in receiver performance using this filer. The Q-enhanced filter redesign ports the existing filter to a new integrated circuit technology which performs better at higher frequencies. The redesign in particular addresses problems in the previous design. The frequency divider design is modified, resistance tuning is added, and additional modifications to the overall filter functionality are implemented. General problems in obtaining an ideal passband shape by eliminating unwanted coupling are addressed. The supporting software for the tuning algorithm is modified to use analog controls and shown to achieve further narrowed bandwidths of 5 MHz and 2.5 MHz at center frequencies of 500 MHz, which are demonstrated to be temperature stable. Future software modifications are described to prepare the existing code base for the new filter design. Potential applications for a Q-enhanced filter include improving the performance of receiver designs. One of the most important performance parameters of a receiver is its spurious response rejection. To explore this behavior, an automated test system is developed to characterize receivers, and four receivers are tested. The test results are presented in a novel graphical display, which is used to evaluate receiver performance and compare receivers. These results motivated the development of a potential modified superheterodyne receiver architecture using the Q-enhanced filter as an image filter and an IF filter. The viability of this receiver design is tested and shown to provide significant improvements to receiver’s spurious rejection response.
Keywords: Receiver; Filter; Spurious response; Q-enhanced; Electrical Engineering (0544)